2010
DOI: 10.1002/hep.23515
|View full text |Cite
|
Sign up to set email alerts
|

Specific Human Leukocyte Antigen Class I and Ii Alleles Associated With Hepatitis C Virus Viremia

Abstract: M ore than 4 million women and men in the United States and 150 million people worldwide are estimated to be hepatitis C virus (HCV) seropositive. 1,2 Most of these individuals are chronically infected with the virus and are at high risk of cirrhosis, hepatocellular carcinoma, and liverrelated death. The natural history of HCV infection, however, is highly variable. Some individuals do not become HCV infected despite high levels of exposure. 3 Other individuals may clear HCV RNA following acute infection, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 60 publications
3
98
5
Order By: Relevance
“…However, it is important to note that mutations at position 2629 already predominate in genotypes 2a, 2b, 3a, and 6a, which might suggest that the protective effect of HLA-B57 could be genotype specific. This interpretation would be in line with recent reports of genotype-dependent effects on the HLAmediated control of HCV (21,22,36). A recent study by Chuang et al (9) indicates the protective effect of HLA-B57 on the control of HCV genotype 2 infections, which could therefore suggest that in genotype 2 infections, the K2629A variant (not tested here) is capable of being recognized or that this protective effect is not related to the targeting of the NS5B KSKKTPMGF epitope.…”
Section: Vol 85 2011 Ctl Escape Mutations In Ns5b Impair Viral Replsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it is important to note that mutations at position 2629 already predominate in genotypes 2a, 2b, 3a, and 6a, which might suggest that the protective effect of HLA-B57 could be genotype specific. This interpretation would be in line with recent reports of genotype-dependent effects on the HLAmediated control of HCV (21,22,36). A recent study by Chuang et al (9) indicates the protective effect of HLA-B57 on the control of HCV genotype 2 infections, which could therefore suggest that in genotype 2 infections, the K2629A variant (not tested here) is capable of being recognized or that this protective effect is not related to the targeting of the NS5B KSKKTPMGF epitope.…”
Section: Vol 85 2011 Ctl Escape Mutations In Ns5b Impair Viral Replsupporting
confidence: 89%
“…Although the mechanisms of spontaneous clearance of hepatitis C virus (HCV) remain poorly understood, the carriage of certain human leukocyte antigen class I (HLA-I) alleles, such as HLA-A03, -A11, -B27, -B57, and -Cw01, has been strongly associated with viral control (22,31,35,45). HLA class I alleles function to present virally derived peptides to circulating CD8 ϩ T cells, which have been independently shown to play a critical role in the control and clearance of HCV infections (24,44).…”
mentioning
confidence: 99%
“…21 The high risk of HCV infection has been confirmed in dialysis patients, drug users, and transfusion patients who had large or repeated exposures to blood. 22,23 In drug users, Kuniholm et al 13 observed no significant relationships between HLA alleles and HCV serostatus in women at high risk of HCV infection from injection drug use. However, in Sardinian transfusion-dependent thalassemia patients, the distribution of HLA class II alleles showed a significant increase of HLA DRB1 Ã 1601 in HCV negative patients, who despite regular blood transfusion program did not show any evidence of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Specific HLA alleles may be possible mediators of host capacity to resist HCV infection and differences in HLA-specific protein expression may affect HLA restricted immune responses. 17 There has been few published data regarding HCV resistance and HLA DR alleles in high risk of exposure populations 12,13,16 and especially patients on hemodialysis. 11,18 We found a significant negative association between HLA DRB1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation